COVERED INTEREST ARBITRAGE UNTUK BEBERAPA VALUTA ASING YANG KUAT TERHADAP RUPIAH - Bahtiar Usman (Universitas Trisakti, 2001)
Economic agents preffered to invest in foreign exchange in recent year. Where circu- lation of money and capital are faster than transaction on goods & services one of the common type of then is arbitrage The high return from one transaction facility will give the high risk, as a result the decision making for such investment in foreign exchange is becoming important The purpose of this study is to do the simulation by using Arbitrage facilities for such investment on foreign exchange. This study will find the best foreign exchange between US Dollar, Deutsche Mark, Poundsterling and Yen, with the bestinterest rate and the best inflation rate for such transaction by using Arbitrage transaction mechanism. in foreign exchange transaction, the speculation risk is very high but this is becoming a reason why this kind of transaction being attractive and obviously more economic agents done this business. When the exchange rates become high, economic agents have a chance to get the high profit because of such differences occurred on exchange rates. The problem is how to manage this situation as well as possible mainly for managers. The role of estimation on foreign exchange for example by knowing the variables that determined foreign exchange rates, is important for trading on foreign exchange. Beside that, Arbitrage can give an additional profit from such investment in a foreign exchange and windfall profit from spread of the foreign exchange.